Solute sources and geochemical processes in Subglacial Lake Whillans, West Antarctica - Michaud A. B.; Skidmore M. L.; Mitchell A. C.; Vick-Majors T. J.; Barbante C.; Turetta C.; Van Gelder W.; Priscu J. C. (Geology, 2016)
Subglacial Lake Whillans (SLW), West Antarctica, is an active component of the subglacial hydrological network located beneath 800 m of ice. The fill and drain behavior of SLW leads to long (years to decades) water residence times relative to those in mountain glacier systems. Here, we present the aqueous geochemistry of the SLW water column and pore waters from a 38-cm-long sediment core. Stable isotopes indicate that the water is primarily sourced from basal-ice melt with a minor contribution from seawater that reaches a maximum of similar to 6% in pore water at the bottom of the sediment core. Silicate weathering products dominate the crustal (non-seawater) component of lake-and pore-water solutes, and there is evidence for cation exchange processes within the clay-rich lake sediments. The crustal solute component ranges from 6 meq L-1 in lake waters to 17 meq L-1 in the deepest pore waters. The pore-water profiles of the major dissolved ions indicate a more concentrated solute source at depth (> 38 cm). The combination of significant seawater and crustal components to SLW lake and sediment pore waters in concert with ion exchange processes result in a weathering regime that contrasts with other subglacial systems. The results also indicate cycling of marine water sourced from the sediments back to the ocean during lake drainage events.